Airman Jennings the Impaler. - JENNINGS, BRANDON DAVIS (Ninth Letter)
The article discusses how Airman Jennings, a technical controller from Okinawa, Japan, was ordered to climb the rooftop of a communications building in the spring of 2002 to guard the shop from Okinawan contractors, who were spreading fresh tar on the rooftop. It notes that Jennings was ordered to stand guard at the rooftop to protect the shop's satellite dishes and was armed with a radio. It mentions of his determination and readiness to protect the shop from the contractors.